2000
DOI: 10.1042/bj3500505
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of tumour necrosis factor-α-related apoptosis-inducing ligand (TRAIL): cysteine-230 plays a critical role in the homotrimerization and biological activity of this novel tumoricidal cytokine

Abstract: We have determined that the mutation of the cysteine-230 residue to either glycine or serine in TRAIL (tumour necrosis factor-alpha-related apoptosis-inducing ligand) results in the formation of a structurally incompetent dimer and a consequent loss of apoptotic activity. Similarly, chemical modification of the thiol residues present in both reduced and Zn(2+)-depleted trimer converts TRAIL into an inactive dimer. We postulate that cysteine-230 plays a critical role in homotrimerization of this tumoricidal cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
4
10
0
Order By: Relevance
“…TRAIL C230A exhibited only 4.4-fold lower affinity with TR2 than wild-type TRAIL, but it did not form a stable trimeric complex and exhibited no apoptotic activity, consistent with previous observations [6,[9][10][11]. Alternative substitutions of Cys230 with Ser, Val, Ile, Met, Leu, Thr, or His gave the same results (data not shown).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…TRAIL C230A exhibited only 4.4-fold lower affinity with TR2 than wild-type TRAIL, but it did not form a stable trimeric complex and exhibited no apoptotic activity, consistent with previous observations [6,[9][10][11]. Alternative substitutions of Cys230 with Ser, Val, Ile, Met, Leu, Thr, or His gave the same results (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…2 and Table 1). Even though the exact homotrimerization constant is not available for wild-type TRAIL, previous SEC and crystallographic studies have shown that wild-type TRAIL exists as a stable trimer in solution, down to at least micromolar concentrations [5,6,11,12]. As expected, wild-type TRAIL was eluted as a trimer with the expected MW of 60 kDa ( 20 kDa · 3) (Fig.…”
Section: Construction and Purification Of Trail C230a -Derived Mutantssupporting
confidence: 57%
See 2 more Smart Citations
“…Oxidation between cysteine residues forms a homodimeric TRAIL. 24 As we and others demonstrated recently, 24,25 the dimeric TRAIL has much lower apoptotic activity than trimeric TRAIL. These data indicate that trimerization is critical for proper TRAIL function.…”
Section: Introductionmentioning
confidence: 85%